Analysis of the Legitimacy of China’s Construction of Islands and Reefs in the South China Sea - Xiaoxiao Li (Law and Economy, 2022)
China has sufficient historical evidence and international law to assert its sovereignty over the South China Sea. China’s construction of islands and reefs in the South China Sea is essentially a man-made accretion, and this behavior is legal and reasonable under international law. The nature of the construction in the South China Sea has not changed before and after the artificial accretion, nor does it harm the rights of neighboring countries. On the contrary, the construction of islands and reefs in the South China Sea not only ensures the safety of navigation channels, but also promotes the development of China and regional countries.